Biennial Premio Gunther : 1993. - Centro de Arte y Comunicación, Buenos Aires; Museu de Arte Contemporãnea da Universidade de São Paulo; Museo Nacional de Bellas Artes, Santiago de Chile (Buenos Aires : [s.n.], 1993)
Garofalo, José ; Garcia, Daniel ; Socolovsky, Paula ; Rolla, Marco Paulo ; Whitaker, Paulo ; Marchezi, Fulvia ; Krause, Rainer ; Caldera, Patricio ; Catrileo, Juan
Biennial Premio Gunther : 1993, IV Biennial, Centro de Arte y Comunicación, Buenos Aires, 27 April - 26 May 1993 / I Biennial, Sao Paulo, Museu de Arte Contemporânea da Universidade de São Paulo, 15 April - 16 May 1993 / II Biennial, Museo Nacional de Bellas Artes - Sala Matta, Santiago de Chile, 6 - 30 May, 1993
boek